The Duracy of Fermentation Effect on the Chemical Quality of Kimchi Krai (Cucumis sativus L.) as Probiotics - Nafisah, Halimatun; Agustini, Rudiana (Jurnal Pijar Mipa, 2024)
This study aims to describe the effect of fermentation duration on the chemical quality of kimchi krai as a food containing probiotics, including total LAB, total titratable acid, pH, antioxidant activity, and level of liking. This research used laboratory experimental methods, and data analysis was done descriptively. Several stages were carried out, including sample making, sample preparation, sample extraction, total LAB test, pH test, total titratable acid test, antioxidant activity test with DPPH method to obtain IC50 value, and organoleptic test. This study used fermentation durations of 8 hours, 16 hours, and 24 hours. The best chemical quality of kimchi krai was obtained in 24-hour fermentation with a total LAB of 6.1x107, pH value decreased from pH 4.75 in 8-hour fermentation to 3.85 in 24-hour fermentation, while for total titratable acid with the highest value of 0.62%, the strongest antioxidant activity with IC50 429.86 ppm. Based on the results, the very weak category includes antioxidant activity in kimchi krai (Cucumis Sativus L.). However, the longer the fermentation process of kimchi krai (Cucumis Sativus L.), the greater the ability to inhibit free radicals.